Glycomimetics Targeting Glycosyltransferases: Synthetic, Computational and Structural Studies of Less‐Polar Conjugates. Issue 21 (13th April 2016) - Ghirardello, Mattia; de las Rivas, Matilde; Lacetera, Alessandra; Delso, Ignacio; Lira‐Navarrete, Erandi; Tejero, Tomás; Martín‐Santamaría, Sonsoles; Hurtado‐Guerrero, Ramón; Merino, Pedro
Abstract: The Leloir donors are nucleotide sugars essential for a variety of glycosyltransferases (GTs) involved in the transfer of a carbohydrate to an acceptor substrate, typically a protein or an oligosaccharide. A series of less‐polar nucleotide sugar analogues derived from uridine have been prepared by replacing one phosphate unit with an alkyl chain. The methodology is based on the radical hydrophosphonylation of alkenes, which allows coupling of allyl glycosyl compounds with a phosphate unit suitable for conjugation to uridine. Two of these compounds, the GalNAc and galactose derivatives, were further tested on a model GT, such as GalNAc‐T2 (an important GT widely distributed in human tissues), to probe that both compounds bound in the medium–high micromolar range. The crystal structure of GalNAc‐T2 with the galactose derivative traps the enzyme in an inactive form; this suggests that compounds only containing the β‐phosphate could be efficient ligands for the enzyme. Computational studies with GalNAc‐T2 corroborate these findings and provide further insights into the mechanism of the catalytic cycle of this family of enzymes. Abstract : Finding active forms : Computational and structural studies with novel glycomimetics derived from uridine provide insights into the catalytic cycle of glycosyltransferases (see figure).